2023
DOI: 10.1371/journal.pgen.1010558
|View full text |Cite
|
Sign up to set email alerts
|

Atp7b-dependent choroid plexus dysfunction causes transient copper deficit and metabolic changes in the developing mouse brain

Abstract: Copper (Cu) has a multifaceted role in brain development, function, and metabolism. Two homologous Cu transporters, Atp7a (Menkes disease protein) and Atp7b (Wilson disease protein), maintain Cu homeostasis in the tissue. Atp7a mediates Cu entry into the brain and activates Cu-dependent enzymes, whereas the role of Atp7b is less clear. We show that during postnatal development Atp7b is necessary for normal morphology and function of choroid plexus (ChPl). Inactivation of Atp7b causes reorganization of ChPl’ cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The displacement of these proteins is specifically triggered by elevated levels of their own ligand, Cu (I), not Cu (II), and is intended to efflux to restore intracellular copper levels 43 45 FDX1 helps convert Cu (II) to the more toxic Cu (I), and in our study, DSF inhibited FDX1 expression, reduced Cu (I) levels, and reduced transport of ATP7A and ATP7B. Interestingly, dysregulation of the Cu transport mechanism in the choroid plexus of Atp7b –/– mice has been demonstrated in recent studies; these mice exhibited low Cu levels in the brain at 4 weeks postnatally, emphasizing the crucial role of ATP7B in Cu accumulation 46 . In summary, the inhibition of CTR1 could regulate the cuproptosis pathway by affecting Cu uptake.…”
Section: Discussionsupporting
confidence: 75%
“…The displacement of these proteins is specifically triggered by elevated levels of their own ligand, Cu (I), not Cu (II), and is intended to efflux to restore intracellular copper levels 43 45 FDX1 helps convert Cu (II) to the more toxic Cu (I), and in our study, DSF inhibited FDX1 expression, reduced Cu (I) levels, and reduced transport of ATP7A and ATP7B. Interestingly, dysregulation of the Cu transport mechanism in the choroid plexus of Atp7b –/– mice has been demonstrated in recent studies; these mice exhibited low Cu levels in the brain at 4 weeks postnatally, emphasizing the crucial role of ATP7B in Cu accumulation 46 . In summary, the inhibition of CTR1 could regulate the cuproptosis pathway by affecting Cu uptake.…”
Section: Discussionsupporting
confidence: 75%
“…124 Lastly, copper is transferred from the cytosol to the TGN lumen by the Cu + -ATPase transporters ATP7A and ATP7B, where it eventually triggers copper-dependent proteins in the secretory pathway. 126…”
Section: Summary Of the Pathways That Mediate Cellular Copper Metabolismmentioning
confidence: 99%
“…To explore how G3BPs regulate cilium length, we performed mass spectrometry to elucidate the protein expression profiles of control cells and G3BP dKO cells after culture in serum‐free medium for 24 h. A total of 105 differentially expressed proteins were identified, including 60 proteins that were significantly upregulated and 45 that were downregulated in G3BP dKO cells relative to control cells (Figure S4A and Table S3, Supporting Information). Among these differentially expressed proteins, we found seven cilium‐related proteins, namely, copper‐transporting ATPase 2 (ATP7B), [ 24 ] collagen alpha‐1 (II) chain (COL2A1), [ 25 ] aspartokinase 1 (AK1), [ 26 ] fatty acid‐binding protein (FABP4), [ 27 ] AKAP12, [ 28 ] serologically defined colon cancer antigen 8 homolog (SDCCAG8), [ 29 ] and pyruvate dehydrogenase (acetyl‐transferring) kinase isozyme 1 (PDK1) (Figure S4B and Table S4, Supporting Information). First, qPCR results showed that the transcript level of SDCCAG8 was downregulated in G3BP dKO cells relative to control cells, which was inconsistent with the mass spectrometry results and that the levels of ATP7B and CoL2A1 were indistinguishable between the two cell lines.…”
Section: Resultsmentioning
confidence: 99%